2019
DOI: 10.1002/cam4.2547
|View full text |Cite
|
Sign up to set email alerts
|

Targeting claudin‐4 enhances chemosensitivity of pancreatic ductal carcinomas

Abstract: Claudin (CLDN) family comprises of protein that form a tight junction, and is involved in regulating polarity and differentiation of cells. Here, we aimed to investigate the effects of inhibiting CLDN4 in pancreatic ductal carcinomas (PDC). We first examined 91 cases of human PDC by immunohistochemistry and found that CLDN4 expression was correlated with tumor invasion, nodal metastasis, and distant metastasis. Anti‐CLDN4 extracellular domain antibody, previously established by us (4D3), inhibited the prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…It is known that the alteration of CLDN4 is tightly linked with the malignant progression of various malignancies and therapeutic resistance. 40 , 41 , 42 Here, we found the obvious downregulation of CLDN4 in TSPEAR-AS2-depleted GC cells and significant upregulation of CLDN4 in TSPEAR-AS2-overexpressed GC cells, identifying that CLDN4 may be a key downstream effector of TSPEAR-AS2 in GC progression ( Figure 6 D).
Figure 6 lncRNA TSPEAR-AS2 Modulates CLDN4 Expression by Competing for miR-1207-5p in GC (A) The qRT-PCR assays were conducted to validate the alteration of key genes in GC cells with TSPEAR-AS2 knockdown.
…”
Section: Resultsmentioning
confidence: 61%
“…It is known that the alteration of CLDN4 is tightly linked with the malignant progression of various malignancies and therapeutic resistance. 40 , 41 , 42 Here, we found the obvious downregulation of CLDN4 in TSPEAR-AS2-depleted GC cells and significant upregulation of CLDN4 in TSPEAR-AS2-overexpressed GC cells, identifying that CLDN4 may be a key downstream effector of TSPEAR-AS2 in GC progression ( Figure 6 D).
Figure 6 lncRNA TSPEAR-AS2 Modulates CLDN4 Expression by Competing for miR-1207-5p in GC (A) The qRT-PCR assays were conducted to validate the alteration of key genes in GC cells with TSPEAR-AS2 knockdown.
…”
Section: Resultsmentioning
confidence: 61%
“…In this study, OSCCs showing nuclear CLDN4 expression were found more strongly correlated with cancer progression than those showing cell membrane CLDN4 expression. Previous studies have shown that CLDN4 forms tight junctions that preserve the cancer microenvironment to accumulate growth factors and maintain extracellular pH in an acidic range [12][13][14]20]. Tight junctions also inhibit the penetration of anticancer drugs into this microenvironment and develop resistance against anticancer drugs [12][13][14]20].…”
Section: Discussionmentioning
confidence: 99%
“…CLDN4 expression is considered as a marker of epithelial differentiation [15][16][17], and its reduced expression is associated with epithelial-mesenchymal transition (EMT) [18,19]. It forms tight junctions, maintains the cancer microenvironment, accumulates growth factors, and inhibits the penetration of anticancer drugs in the cells [12][13][14]20]. In contrast, CLDN4 proteins which do not form tight junctions, act as ligand for integrin signaling and promote survival signals and stemness as found in undifferentiated gastric cancer cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, overexpression of claudin 4 in PDAC has been found not only in primary tumors and metastases but also in precursor lesions, making it a potential target for early diagnosis and treatment 75 . Moreover, the role of claudin 4 in the development of chemoresistance by inhibiting access of therapeutic agents to tumor cells has been reported in several studies 31 - 33 . Therefore, agents able to interfere with the function of this protein may improve therapeutic efficacy of chemotherapeutic regimens, reduce the side effects, and improve patients' quality of life.…”
Section: Search Strategy and Target Selectionmentioning
confidence: 99%
“…Claudins have functional and structural activity in the composition of the tight junction barrier in normal epithelium 3 , 73 , 74 . As part of the tight junction barrier, claudins have several roles in normal cell functioning, including the maintenance of cell polarity and adhesion, as well as controlling of traffic of substances between cells 31 . Several studies have shown that claudin expression is dysregulated in various types of cancer, where it contributes to tumor progression and invasion 3 , 73 .…”
Section: Search Strategy and Target Selectionmentioning
confidence: 99%